(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
Widespread coring of the Eastern Mediterranean Basin has outlined the existence of a systematic relation between lithology of debris flow deposits and physiographic setting. Whilst the topographic highs are characterized by pelagic sedimentation, the basin floors are alternatively subject to pelagic sedimentation and re-sedimentation pro cesses. Amongst the latters, turbidity flows and debris flows are the most common transport mechanisms. In this paper we present the study of the debris flow pro cess in the Ionian Sea using visual description of cores, grain size, carbonate content and smear slide analysis carried out on gravity and piston cores recovered over the past 20 years. A distinction has been made between debris flow deposits originating from the continental margins (North Africa and Malta Escarpment) and those emplaced in the small basins amidst the Calabrian and Mediterranean ridges "Cobblestone Topography". As a result of the difference in setting, the former debris flow deposits include a great variety of lithologies and ages whilst the latter involve the pelagic sediments forming the typical Eastern Mediterranean Plio-Quaternary succession. A detailed study of clast and matrix structures makes it possible to describe the flows in terms of existing classifications of sediment gravity flows and to assume a clast support mechanism. Finally, biostratigraphy coupled with the presence of widespread marker beds enabled us to estimate the age of emplacement of the deposits and to hypothesize a triggering mechanism for flow initiation. Three flows are strictly related to the pelagic turbidite named homogenite, triggered by the explosive eruption of the Santorini volcano (Minoan eruption) and therefore have an estimated age of 3,500 BP. The other deposits have ages ranging from 9,000 BP to about 70,000 BP and were originated by debris flows triggered by events such as earthquakes and glacial low sea level stands.